Differences in spine volumetric bone mineral density between grade 1 vertebral fracture and non-fractured participants in the China action on spine and hip status study - Liu, Yandong; Yu, Aihong; Li, Kai; Wang, Ling; Huang, Pengju; Geng, Jian; Zhang, Yong; Duanmu, Yang-yang; Blake, Glen M.; Cheng, Xiaoguang (Frontiers in Endocrinology, 2022)
Purpose: This study evaluated the prevalence of vertebral fractures (VF) in middle-aged and elderly Chinese men and women and explored the differences in lumbar spine volumetric bone mineral density (vBMD) derived from quantitative CT (QCT) between those with a grade 1 vertebral fracture and non-fractured individuals. Materials & Methods: 3,457 participants were enrolled in the China Action on Spine and Hip Status (CASH) study and had upper abdominal CT examinations. Vertebral fractures were identified by Genant’s semi-quantitative method from lateral CT scout views or CT sagittal views. L1-3 vBMD was measured by Mindways QCT Pro v5.0 software. The characteristics of different fracture severity groups were compared using one-way ANOVA, independent-samples t-tests, and Kruskal-Wallis H-tests. Results: 1267 males (aged 62.77±9.20 years) and 2170 females (aged 61.41±9.01 years) were included in the analysis. In men, the prevalence of VF increased from 14.7% at age＜50 years to 23.2% at age ≥70 years, and in women from 5.1% at age＜50 years to 33.0% at age ≥70 years. Differences in mean age and vBMD were found between the different fracture grade groups. After age stratification, vBMD differences in men aged < 50 years old disappeared (p = 0.162) but remained in the older age bands. There was no significant difference in mean vBMD between those with multiple mild fractures and those with a single mild fracture. Conclusion: In women, the prevalence of VF increased rapidly after age 50, while it grew more slowly in men. In general, with the exception of men ＜50 years old, participants with a grade 1 VF had lower vBMD than non-fractured individuals. The majority of women younger than 50 with a grade 1 VF had normal bone mass. We recommend that a vertebral height reduction ratio of <25% be diagnosed as a deformity rather than a fracture in people under the age of 50. The presence of multiple mild fractured vertebrae does not imply lower BMD.